SYSTEM ANALYSIS AS THE GENERAL METHODOLOGICAL BASIS OF TOWN-PLANNING DESIGNING - Pozdnyakov, Andrey Leonidovich; Pozdnyakova, Ekaterina Viktorovna; Zvjagintseva, Marina Mikhaelovana; Barsova, Olga Yurevna (Journal of Applied Engineering Science, 2018)
Proposals for the organization of the territory, the formation of the territorial structure of the "ecological framework" of regional settlement systems are the most important, but not the only result of the application of urban ecology to regional resettlement. It is also necessary to develop a system of common measures to protect air, water and soil and vegetation cover from the impact on the natural environment of urban agglomerations, individual large cities, large recreational and tourist areas. The system of urban ecological restrictions is of particular importance. In this regard, it is extremely necessary to carry out a complex of research and development projects to establish valid urban environmental restrictions, primarily the level of concentration and location of enterprises in various industries, as well as the growth of cities in various natural areas and economic regions of the country. Urboecological restrictions should be based on the threshold values of enterprise capacity, urban population, freight turnover, intensity of recreational flows and loads on the landscape, and regimes of specially protected areas.
Keywords: Systems; restriction; regions; methodology; enterprises; ecology